Analysis by Metabolomics and Transcriptomics for the Energy Metabolism Disorder and the Aryl Hydrocarbon Receptor Activation in Male Reproduction of Mice and GC-2spd Cells Exposed to PM2.5 - Shi, Fuquan; Zhang, Zhonghao; Wang, Jiankang; Wang, Yimeng; Deng, Jiuyang; Zeng, Yingfei; Zou, Peng; Ling, Xi; Han, Fei; Liu, Jinyi; Ao, Lin; Cao, Jia (Frontiers in Endocrinology, 2022)
Fine particulate matter (PM2.5)-induced male reproductive toxicity arouses global public health concerns. However, the mechanisms of toxicity remain unclear. This study aimed to further investigate toxicity pathways by exposure to PM2.5in vitro and in vivo through the application of metabolomics and transcriptomics. In vitro, spermatocyte-derived GC-2spd cells were treated with 0, 25, 50, 100 μg/mL PM2.5 for 48 h. In vivo, the real-world exposure of PM2.5 for mouse was established. Forty-five male C57BL/6 mice were exposed to filtered air, unfiltered air, and concentrated ambient PM2.5 in Tangshan of China for 8 weeks, respectively. The results in vitro and in vivo showed that PM2.5 exposure inhibited GC-2spd cell proliferation and reduced sperm motility. Mitochondrial damage was observed after PM2.5 treatment. Increased Humanin and MOTS-c levels and decreased mitochondrial respiratory indicated that mitochondrial function was disturbed. Furthermore, nontargeted metabolomics analysis revealed that PM2.5 exposure could disturb the citrate cycle (TCA cycle) and reduce amino acids and nucleotide synthesis. Mechanically, the aryl hydrocarbon receptor (AhR) pathway was activated after exposure to PM2.5, with a significant increase in CYP1A1 expression. Further studies showed that PM2.5 exposure significantly increased both intracellular and mitochondrial reactive oxygen species (ROS) and activated NRF2 antioxidative pathway. With the RNA-sequencing technique, the differentially expressed genes induced by PM2.5 exposure were mainly enriched in the metabolism of xenobiotics by the cytochrome P450 pathway, of which Cyp1a1 was the most significantly changed gene. Our findings demonstrated that PM2.5 exposure could induce spermatocyte damage and energy metabolism disorder. The activation of the aryl hydrocarbon receptor might be involved in the mechanism of male reproductive toxicity.